Thinking beyond Chatbots’ Threat to Education: Visualizations to Elucidate the Writing or Coding Process - Adhikari, Badri (Education sciences, 2023)
Despite overwhelming evidence to the contrary, educational practices continue to be predominantly centered around outcome-oriented approaches. These practices are now thoroughly disrupted by the recent accessibility of online resources and chatbots. Among the most affected subjects are writing and computer programming. As educators transform their teaching practices to account for this disruption, it is important to note that writing and computer programming play a critical role in the development of logical and computational thinking. For instance, what and how we write shapes our thinking and sets us on the path of self-directed learning. Likewise, computer programming plays a similar role in the development of computational thinking. While most educators understand that “process” and “outcome” are both crucial and inseparable, providing constructive feedback on a learner’s formative process is challenging in most educational settings. To address this long-standing issue in education, this work presents Process Visualizations, a new set of interactive data visualizations that summarize the inherent and taught capabilities of a learner’s writing or programming process. These visualizations provide insightful, empowering, and personalized process-oriented feedback to learners and help to improve cognitive and metacognitive skills. Likewise, they assist educators in enhancing their effectiveness in the process-aware teaching of writing or computer programming. The toolbox for generating the visualizations, named Process Feedback, is ready to be tested by educators and learners and is publicly available as a website.